Investigate the effect of Bacterial Vaginosis-associated bacteria on the efficacy of Anti-HIV therapy - Davies, Alessandra Unterpertinger (Department of Integrative Biomedical Sciences (IBMS), 2025)
Infection with human immunodeficiency virus type 1 (HIV-1) remains one of the leading causes of death worldwide with young women in sub-Saharan Africa the most affected. Although pre-exposure prophylaxis (PrEP) with antiretroviral (ARV) drugs such as tenofovir (TFV) and emtricitabine have been shown to protect men who have sex with men (MSM) from HIV infection, PrEP trials have not been as successful for women. Although this disparity is most likely multifactorial, studies have shown an association between decreased drug efficacy and increased diversity of the female genital tract (FGT) microbiome. The shift from a homogenous Lactobacillus spp. dominated population to one defined by bacterial vaginosis (BV) associated bacteria such as Gardnerella spp. not only increased the risk of HIV acquisition but also reduced the ability of ARVs to protect against infection. Additionally, Lactobacillus crispatus (L. crispatus) was used in this study because it has previously shown to suppress the growth of Gardnerella vaginalis (G. vaginalis) in a porcine vaginal mucosa model. Recently, it was confirmed that metabolism of TFV by G. vaginalis reduced the extracellular level of ARV available to inhibit infection. We hypothesised that G. vaginalis not only internalises/metabolises TFV but also other ARVs and that the presence of L. crispatus could negate this effect. The main objective of this study was to investigate if exposure of TFV, tenofovir disoproxil fumarate (TDF), maraviroc (MVC) and abacavir (ABC) to G. vaginalis reduced extracellular ARV drug concentrations to a level unable to inhibit HIV infection and to determine whether L. crispatus was able to counteract this effect. G. vaginalis and L. crispatus were grown for 24 hours (t24) in the presence and absence of drugs and cells were lysed and the culture medium harvested before (t0) and after incubation. Using mass spectrometry, we found that G. vaginalis and L. crispatus took up not only TFV but also ABC and MVC. However, this uptake did not correspond to a significant decrease in extracellular ARV drugs. Extracellular and intracellular TFV, TDF, and MVC samples were added to the reporter cell line, TZM-bl, during infection with infectious molecular clones and pseudovirus infection. Intracellular TDF, TFV, and MVC at t24 had no impact on HIV infectivity, suggesting that the concentration of ARVs internalised by the bacteria was not sufficient to inhibit infection to detectable levels. At t0, extracellular ARVs inhibited infection by approximately 40% whereas at t24, inhibition decreased to approximately 20%. Therefore, incubation with G. vaginalis consistently reduced drug efficacy 2-fold, irrespective of the ARV, although this change was not statistically significant. Although L. crispatus had a similar effect as G. vaginalis on TFV and TDF 12 efficacy, extracellular MVC present after incubation with L. crispatus inhibited infection by 50%, similar to t0. Therefore, L. crispatus, despite internalising MVC, had no effect on the drug's efficacy. Residual extracellular TDF and TFV at t24 obtained from co-culture samples also lowered inhibition 2-fold, indicating that L. crispatus did not impact the effect of G. vaginalis culture had on drug efficacy. However, extracellular MVC present after co-culture, inhibited infection by 50%, similar to t0. Therefore, L. crispatus, was able to abrogate the effect of G. vaginalis on MVC efficacy. We showed that G. vaginalis not only internalised MVC, an entry inhibitor, but reduced its efficacy and this effect was lost in the presence of L. crispatus. This finding was contrary to what was observed for TFV and TDF, suggesting that the effect of G. vaginalis on ARV efficacy was dependent on the type of drug. These findings confirm the importance of the FGT microbiome in modulating the efficacy of ARV PrEP. Therefore, PrEP formulations with TFV, TDF, and ABC might not be as protective for women with BV compared to those that are BV-negative. Therefore, it is recommended that individuals at high risk of acquiring HIV should be regularly screened for BV.